2005
DOI: 10.1037/0096-3445.134.4.552
|View full text |Cite
|
Sign up to set email alerts
|

The Automaticity of Visual Statistical Learning.

Abstract: Recent studies of visual statistical learning (VSL) have demonstrated that statistical regularities in sequences of visual stimuli can be automatically extracted, even without intent or awareness. Despite much work on this topic, however, several fundamental questions remain about the nature of VSL. In particular, previous experiments have not explored the underlying units over which VSL operates. In a sequence of colored shapes, for example, does VSL operate over each feature dimension independently, or over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

76
757
16
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 690 publications
(855 citation statements)
references
References 73 publications
76
757
16
6
Order By: Relevance
“…Indeed, both segmentation cues are available throughout linguistic development (i.e., since an early age-e.g., Johnson & Jusczyk, 2001;Kirkham, Slemmer & Johnson, 2002;-and in adulthood-e.g., Mattys, 2004, but only coarticulation is speech-specific, and hence may be processed by an encapsulated system that may operate quite independently of attention resources. On the contrary, TP computation relies on a domain-general learning mechanism (e.g., Fiser & Aslin, 2001;Perruchet & Pacton, 2006;Turk-Browne et al, 2005) that may be more sensitive to attention resources and hence to cognitive load. A recent study by Astheimer and Sanders (2009) also suggests that domain specificity could play a role in the allocation of selective attention to word onsets.…”
Section: General R R Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, both segmentation cues are available throughout linguistic development (i.e., since an early age-e.g., Johnson & Jusczyk, 2001;Kirkham, Slemmer & Johnson, 2002;-and in adulthood-e.g., Mattys, 2004, but only coarticulation is speech-specific, and hence may be processed by an encapsulated system that may operate quite independently of attention resources. On the contrary, TP computation relies on a domain-general learning mechanism (e.g., Fiser & Aslin, 2001;Perruchet & Pacton, 2006;Turk-Browne et al, 2005) that may be more sensitive to attention resources and hence to cognitive load. A recent study by Astheimer and Sanders (2009) also suggests that domain specificity could play a role in the allocation of selective attention to word onsets.…”
Section: General R R Discussionmentioning
confidence: 99%
“…They were informed that the text they would read later on had no direct relation to the auditory and visual stimuli presented in the first phase. These instructions aimed at forcing participants to allocate their attention to both the visual and auditory streams, in a nonetheless incidental passive learning situation (see Turk-Browne, Jungé, & Scholl, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Those studies led to the emergence of models centered on the need for learners' attentional involvement (e.g., Mackintosh, 1975). Since then, empirical data suggesting that learning does not occur without a minimal level of attention have accumulated, especially in the area of implicit, nonintentional forms of learning, which has 1 Turk-Browne et al (2005) reported successful learning of relationships between visual shapes of a given color when the related items are interrupted by irrelevant items from another color stream. Turk-Browne et al's study was not directly aimed at studying nonadjacent dependencies, and as discussed by the authors, the results are only suggestive of the possibility of what they called "interrupted statistical learning."…”
Section: A Unitary View Of Adjacent and Nonadjacentmentioning
confidence: 99%
“…Statistical learning has been demonstrated both when stimuli are presented passively without any explicit task (e.g., Saffran et al 1999;Aslin 2001, 2002;Toro et al 2005), and when participants are engaged in a cover task unrelated to the underlying pattern (Saffran et al 1997, Turk-Browne et al 2005). In addition, statistical learning seems to be unaffected by the precise instructions given to participants (Arcuili et al 2014;Batterink et al 2015).…”
mentioning
confidence: 99%